Response of the Black Sea Zooplankton to the Marine Heat Wave 2010: Case of the Sevastopol Bay - Alexandra Gubanova; Katerina Goubanova; Olga Krivenko; Kremena Stefanova; Oksana Garbazey; Vladimir Belokopytov; Tatiana Liashko; Elitsa Stefanova (Journal of Marine Science and Engineering, 2022)
Global warming is increasing the frequency and severity of the marine heat waves, which poses a serious threat to the marine ecosystem. This study analyzes seasonal and interannual dynamics in the abundance and structure of the mesozooplankton community in Sevastopol Bay based on bi-monthly routine observations over 2003–2014. The focus is on the impact of the summer 2010 marine heat wave (MHW2010) on crustaceans belonging to different ecological groups. As a response to the MHW2010, three warm-water species (O. davisae, A. tonsa and P. avirostris) exhibiting the maximum seasonal density in latter summer showed a sharp increase in the annual abundance and their share in the mesozooplankton community. The increase in the annual abundance in 2010 of the eurythermal species P. parvus and P. polyphemoides exhibiting seasonal peaks in spring and autumn is not related to the MHW2010 but can be explained by a rise of temperature in the first part of the year. O. davisae and A. tonsa showed the most pronounced response among the species to the MHW2010, confirming that non-native species exhibited great flexibility as an adaptive response to environmental changes, especially in the case of climate warming. Among crustaceans observed in this study, O. davisae can be considered as an indicator of the environmental conditions associated with the warming of the Black Sea and the Mediterranean basin as a whole.